RARS1‐related hypomyelinating leukodystrophy: Expanding the spectrum. Issue 1 (8th December 2019) - Mendes, Marisa I.; Green, Lydia M. C.; Bertini, Enrico; Tonduti, Davide; Aiello, Chiara; Smith, Desiree; Salsano, Ettore; Beerepoot, Shanice; Hertecant, Jozef; von Spiczak, Sarah; Livingston, John H.; Emrick, Lisa; et al.
Abstract: Objective: Biallelic variants in RARS1, encoding the cytoplasmic tRNA synthetase for arginine (ArgRS), cause a hypomyelinating leukodystrophy. This study aimed to investigate clinical, neuroradiological and genetic features of patients with RARS1 ‐related disease, and to identify possible genotype‐phenotype relationships. Methods: We performed a multinational cross‐sectional survey among 20 patients with biallelic RARS1 variants identified by next‐generation sequencing techniques. Clinical data, brain MRI findings and genetic results were analyzed. Additionally, ArgRS activity was measured in fibroblasts of four patients, and translation of long and short ArgRS isoforms was quantified by western blot. Results: Clinical presentation ranged from severe (onset in the first 3 months, usually with refractory epilepsy and early brain atrophy), to intermediate (onset in the first year with nystagmus and spasticity), and mild (onset around or after 12 months with minimal cognitive impairment and preserved independent walking). The most frequent RARS1 variant, c.5A>G, led to mild or intermediate phenotypes, whereas truncating variants and variants affecting amino acids close to the ArgRS active centre led to severe phenotypes. ArgRS activity was significantly reduced in three patients with intermediate and severe phenotypes; in a fourth patient with intermediate to severe presentation, we measured normal ArgRS activity, but found translation mainly of the short instead of the long ArgRS isoform. Interpretation: Variants in RARS1 impair ArgRS activity and do not only lead to a classic hypomyelination presentation with nystagmus and spasticity, but to a wide spectrum, ranging from severe, early‐onset epileptic encephalopathy with brain atrophy to mild disease with relatively preserved myelination.